Development of a mobile augmented reality navigation application for wheelchair users - Neo, Elaine Kai Wen (2019)
In an urban landscape like Singapore, travelling is often a challenge for wheelchair users due to the large number of physical obstacles like stairs, kerbs and escalators. Normally, wheelchair users have to figure out the most optimal path on their own and this results in precious time wastage. Therefore, the objective of this project is to develop a mobile application to guide wheelchair-users to their destinations. The methodology of this project is to utilise Augmented Reality to provide a seamless navigation experience for wheelchair users and a platform to map out wheelchair-accessible routes. This report focuses on the implementation of cloud storage to store wheelchair-accessible routes and user data and gamification to incentivise volunteers to map out routes.